Analog of the Liouville Equation and BBGKY Hierarchy for a System of Hard Spheres with Inelastic Collisions - Petrina, D.Ya.; Caraffini, G.L. (Український математичний журнал, 2005)
Dynamics of a system of hard spheres with inelastic collisions is investigated. This system is a model for granular flow. The map induced by a shift along the trajectory does not preserve the volume of the phase space, and the corresponding Jacobian is different from one. A special distribution function is defined as the product of the usual distribution function and the squared Jacobian. For this distribution function, the Liouville equation with boundary condition is derived. A sequence of correlation functions is defined for canonical and grand canonical ensemble. The generalized BBGKY hierarchy and boundary condition are deduced for correlation functions. Досліджується динаміка твердих сфер з непружним розсіянням. Така система є моделлю для гранульованих потоків. Відображення, індуковане зсувом уздовж траєкторій, не зберігає об'єм фазового простору, а відповідний якобіан є відмінним від одиниці. Визначено спеціальну функцію розподілу як добуток звичайної функції розподілу та квадрата якобіана. Для цієї функції розподілу виведено рівняння Ліувілля з граничними умовами. Послідовність кореляційних функцій визначено для канонічного та великого канонічного ансамблів. Для кореляційних функцій виведено узагальнену ієрархію ББГКІ та відповідні граничні умови.